SINTESIS DAN KARAKTERISASI Fe-TiO2, N-TiO2, DAN Fe-N-TiO2 - , ARIEF RAHMAN HAKIM, Prof. Dr. Triyono, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Synthesis and characterization of Fe-TiO2, N-TiO2, and Fe-N-TiO2 have been carried out. This research was done to determine the effect of dopant concentration of 2.5, 5.0, and 7.5% w/w on the band gap energy of TiO2 and the effect of single and double dopants to the band gap energy of TiO2. All materials have been synthesized by using impregnation method with TiO2 as precursor, FeCl3.6H2O salt as Fe3+ ions source, and urea as nitrogen source. All samples were characterized by using FT-IR spectroscopy, UV-Vis specular reflectance spectroscopy, and X-ray diffraction. The results showed that the optimum band gap energy of Fe-TiO2 and N-TiO2 yielded from the dopant variation were 3.10 and 3.07 eV. Compared to band gap energy of single doped-TiO2 and pure TiO2, Fe-N-codoped TiO2 had the smallest band gap energy with the optimum value of 2.96 eV. The presence of dopant in TiO2 introduced new level energy between valence and conduction bands of TiO2 so the band gap energy decreased. Fe-N-TiO2 has the smallest band gap energy due to the synergistic effect of new levels energy above valence band and below conduction band of TiO2 induced by both of Fe3+ ions and nitrogen. The presence of dopant into TiO2 not only affect the electronic structure but also crystalline structure of TiO2. All synthesized materials have lower crystallinity compared to pure TiO2, where Fe-N-TiO2 has the lowest crystallinity due to the presence of double dopants in TiO2.